REMITTANCE AND THE ECONOMY: THE NIGERIAN EXPERIENCE (A REVIEW) - Onwuchekwa Raphael IHEKE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Migration is a basic major component of population dynamics which is characterized by deliberate rational decision of the migrant. This phenomenon has been viewed differently by different people, with some mentioning it as a cause of degradation of rural and urban ecological resources. Some associate the spread of HIV/AIDs and recently the Ebola Virus Disease (EVD). The most positive and powerful outcome of migration is remittance income. The significant contribution of international remittances to the stability and sustainable growth prospects of developing countries cannot be overemphasized. Remittances have not only grown strongly in a positive direction, but these inflows have also exhibited a much more stability than other private capital inflows and Overseas Development Assistance (ODA). Remittances are playing an increasingly large role in the economies of many countries, contributing to economic growth and to the livelihoods of people.